Microfiltration Membrane Assisted CO2 Diffuser for Algae Cultivation - Muhammad Idris Lutfi, U. A.; Hizam, S. M.; Lau, K. S.; Md Nordin, N. A. H.; Bilad, M. R.; Putra, Z. A.; Wirzal, M. D. H. (Journal of Applied Membrane Science & Technology, 2018)
The aim of this paper is to cover on the feasibility of using algae as an alternative to capture CO2. As such, comparison between a membrane diffuser and a bubble diffuser in terms of its performance in the cultivation of algae has been made. This work utilized PVDF flat sheet membrane with only air and pure CO2 as the feed gas and the diffusion method used was compared between membrane diffuser and a bubble diffuser. In the experiment, the feed gas flows through the membrane diffuser in which the algae suspension utilized the CO2 for its growth. The biomass contents of four different samples have been determined using the dry weight of the algae suspension samples, which is obtained by drying the samples in an oven overnight at 105ËšC. The algae suspension with the membrane diffuser was able to remove CO2 feasibly while showing better performance with respect to algae cultivation in comparison to the bubble diffuser. Results showed the maximum average biomass content of the samples that used membrane diffuser had higher value of 0.325 g/L when a 1:1 ratio of air and CO2 was used in the feed stream and 0.275 g/L when using pure air as the feed stream. Thus, it has been shown that membrane diffuser is better than a bubble diffuser owing to its larger effective surface area.